Homosexuality as Deviance. The Case of the Gay Police Officer - Burke, Marc E. (The British journal of criminology, 1994)
Using interview data transcribed from original interviews with 36 gay, lesbian, or bisexual currently serving and retired police officers, this article considers the deviance value of a non-heterosexual orienlational status within the police organization and attempts a preliminary assessment of its impact on individual police officers. It is suggested that the discrepant status of homosexuality in law, the machismo sub-culture of the police and the role of the police as regulators of deviance all make it difficult for the police to adopt or accept a non-conformist orientation. The status of lesbianism is also examined in relation to police culture and it is further suggested that the experiences of women as deviant' in this regard may not be analogous to those of their male colleagues. Illustrations of how officers often live double' as opposed to integrated' lives as a result of their predicament are offered, and it is proposed that the stress caused by leading two discrete existences may be detrimental to mental health and significant in the ability of officers to perform effectively at work, or form stable or satisfying personal relationships